Efficiency in hospital care in Brazilian capitals for the period 2014-2017. - do Nascimento Cavalcanti, Ivanessa Thaiane; Rosa de Amorim, Inara; Azevedo Fraga, Joana; de Moura Ferreira Júnior, Hamilton (JBES: Brazilian Journal of Health Economics / Jornal Brasileiro de Economia da Saúde)
Objective: Analyze the level of efficiency of the hospital care in the Brazilian capitals and the Federal District between the years 2014 to 2017. Methods: The investigation method used was the Data Envelopment Analysis to estimate resource the resource efficiency levels. Results: The results indicate that there are differences in the level of efficiency of the state capitals and the Federal District, making it possible to develop the potential of inefficient units, in order to increase technical efficiency in hospital care. Conclusion: Analyzing the use of public resources helps to identify whether resources are being applied efficiently and when not, they signal the need for decision making that is more consistent with the reality of each capital.